Solid electrolytic capacitor, smoothing circuit and filter circuit, and method for manufacturing a solid electrolytic capacitor
Patent Information
- Application Number
- JP2025058646
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0022】 本発明によれば、固体電解コンデンサの耐電圧を高くすることができる。
Smart Images

Figure 2026165968000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolytic capacitor, a method for manufacturing the same, and a smoothing circuit and a filter circuit including the solid electrolytic capacitor.
Background Art
[0002] Capacitors are used in a variety of applications, and are particularly widely used in filter circuits. Examples of the filter circuit include a low-pass filter, a high-pass filter, a band-pass filter, and a ripple filter also referred to as a smoothing circuit. The smoothing circuit is provided in a power converter, and a smoothing capacitor is incorporated in this smoothing circuit. The power converter converts power from an AC power source into DC power by a converter circuit, and converts this DC power into desired AC power by an inverter circuit. The smoothing circuit is interposed between the converter circuit and the inverter circuit, suppresses and smoothes DC pulsation output from the converter circuit, and then inputs the resulting signal to the inverter circuit.
[0003] With the recent increase in power capacity, the demand for higher capacitance of capacitors has been growing. Electrolytic capacitors are easier to achieve higher capacitance than film capacitors, and can easily meet this demand for higher capacitance. An electrolytic capacitor includes a valve action metal such as tantalum or aluminum as an anode foil and a cathode body. The anode foil is enlarged in surface area by forming the valve action metal into a shape such as a sintered body or an etched foil, and has a dielectric film on the enlarged surface by a treatment such as anodization. An electrolyte is interposed between the anode foil and the cathode body.
[0004] Electrolytic capacitors can achieve a large capacitance and meet the demand for high capacitance because the specific surface area of the anode foil can be increased through a surface expansion process. Furthermore, electrolytic capacitors contain an electrolyte in the form of a liquid electrolyte. Since the liquid electrolyte can penetrate deep into the expanded surface of the anode foil, the contact area with the dielectric film can be increased. Therefore, the capacitance of electrolytic capacitors can be further increased, making them suitable for the high capacitance demands associated with the recent increase in power. However, the liquid electrolyte evaporates and dissipates to the outside over time, causing the electrolytic capacitor to experience a decrease in capacitance and an increase in electrostatic loss tangent over time, eventually leading to dry-out.
[0005] Therefore, among electrolytic capacitors, solid electrolytic capacitors, which use a solid electrolyte, are attracting attention. Solid electrolytic capacitors are free from or have suppressed effects from electrolyte drying. In addition, solid electrolytic capacitors have the advantage of having a low equivalent series resistance (ESR).
[0006] Known solid electrolytes include manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes. In recent years, conductive polymers derived from monomers with π-conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), have rapidly become popular as solid electrolytes due to their slow reaction rates and excellent adhesion to dielectric films. Conductive polymers utilize acid compounds such as polyanions as dopants, and also possess substructures within the monomer molecule that act as dopants, resulting in high conductivity. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2003-160647 [Patent Document 2] Japanese Patent Publication No. 2008-258224 [Overview of the project] [Problems that the invention aims to solve]
[0008] With the recent increase in power, capacitors with higher voltage ratings are required. For example, in fields such as power electronics, capacitors with high voltage ratings exceeding 300V are expected. Electrolytic capacitors using electrolytes can withstand high voltages due to the defect repair effect of the dielectric film by the electrolyte, but even such electrolytic capacitors do not easily meet the requirement for high voltage ratings. Moreover, solid electrolytic capacitors have difficulty meeting high voltage ratings compared to electrolytic capacitors using electrolytes, due to considerations of adhesion to the anode foil and the defect repair effect of the dielectric film.
[0009] The present invention was proposed to solve the above problems, and its objective is to provide a high-voltage solid electrolytic capacitor, a method for manufacturing the solid electrolytic capacitor, and a smoothing circuit and a filter circuit equipped with the solid electrolytic capacitor. [Means for solving the problem]
[0010] When a solid electrolytic capacitor is subjected to a high voltage of 300V or more, a short circuit often occurs in the edge region of the anode foil. Even in the case of so-called hybrid type solid electrolytic capacitors that use both liquid electrolyte and solid electrolyte, a short circuit can sometimes be found in the edge region of the anode foil. As a result of diligent research by the inventors, one of the factors causing the voltage withstand capability of solid electrolytic capacitors has been identified as follows.
[0011] In other words, the amount of conductive polymer adhering to the edge region of the anode foil tends to be greater than in the foil surface regions other than the edge region. Furthermore, conductive polymer is incorporated into the conduction path of leakage current generated by defects in the dielectric film, and if the amount of conductive polymer in the conduction path is large, the resistance of the conduction path decreases, resulting in a larger leakage current. Consequently, a large localized current is more likely to flow in the edge region of the anode foil. Heat generated by overcurrent accelerates the deterioration of the dielectric film. Therefore, the amount of conductive polymer adhering to the edge region is one of the causes of the decrease in the withstand voltage of solid electrolytic capacitors to which high voltage is applied.
[0012] Therefore, in order to solve the above problems, the solid electrolytic capacitor of this embodiment comprises an anode foil having a dielectric film with a withstand voltage of 300V or more, a cathode body facing the anode foil, and a conductive polymer interposed between the anode foil and the cathode body, the sulfur contained in its molecular structure, and the sulfur intensity ratio per unit area attached to the edge region of the anode foil is 1.92 or less compared to the sulfur per unit area attached to the foil surface region other than the edge region.
[0013] The sulfur intensity ratio correlates with the ratio of the amount of conductive polymer adhering to the edge region and the foil surface region. This solid electrolytic capacitor reduces the leakage current flowing through the edge region by relatively decreasing the amount of conductive polymer adhering to the edge region, thereby reducing the conduction path in the edge region. As a result, the probability of short circuits occurring at the edge region of the anode foil is reduced, and the solid electrolytic capacitor has a voltage withstand capability of at least 300V.
[0014] The sulfur intensity ratio may be set to 1.71 or less.
[0015] The system may further include an electrolyte, the electrolyte may contain 20 wt% or more of a polymer component in the total amount of the electrolyte.
[0016] The polymer component may be a polyol or a derivative thereof having one or more alkylene oxide groups added and a molecular weight of 600 or more.
[0017] A solid electrolyte layer containing the conductive polymer is formed, and the solid electrolyte layer may contain a compound having a hydroxyl group and a boiling point of 150°C or higher.
[0018] The compound may be ethylene glycol, diethylene glycol, triethylene glycol, polyoxyethylene glycol, glycerin, polyglycerin, or a combination of these.
[0019] A smoothing circuit equipped with this solid electrolytic capacitor is also one embodiment of the present invention that solves the above problems.
[0020] A filter circuit including this solid electrolytic capacitor is also one aspect of the present invention that solves the above problems.
[0021] Further, to solve the above problems, a method for manufacturing a solid electrolytic capacitor according to the present embodiment includes: an anode foil forming step of forming an anode foil; a cathode body forming step of forming a cathode body; and an electrolyte layer forming step of disposing a conductive polymer containing sulfur in its molecular structure on the surface of the anode foil, wherein the anode foil forming step includes a chemical conversion step of forming a dielectric film having a withstand voltage of 300V or higher on the anode foil by a chemical conversion treatment with an applied voltage of 300V or higher, and the electrolyte layer forming step includes an adjusting step of adjusting so that the intensity ratio of the sulfur per unit area adhering to the end region of the anode foil is 1.92 or less relative to the sulfur per unit area adhering to the foil surface region other than the end region. [Effects of the Invention]
[0022] According to the present invention, the withstand voltage of a solid electrolytic capacitor can be increased. [Brief Description of the Drawings]
[0023] [Figure 1] This is a model diagram showing regions in an anode foil. [Figure 2] This is an example of a smoothing circuit including a solid electrolytic capacitor. [Figure 3] This is an example of a filter circuit including a solid electrolytic capacitor. [Figure 4] This is a graph for measuring the withstand voltage of the dielectric film of an anode foil. [Figure 5] This is a graph showing the relationship between the sulfur intensity ratio R and the withstand voltage of a hybrid-type solid electrolytic capacitor. [Figure 6] This is a graph showing the relationship between the withstand voltage of the dielectric film of an anode foil and the improvement value of the withstand voltage of a solid electrolytic capacitor. [Figure 7] This is a graph showing the relationship between the sulfur intensity ratio R and the withstand voltage of a solid electrolytic capacitor using only a conductive polymer. [Modes for carrying out the invention]
[0024] The following describes a solid electrolytic capacitor according to an embodiment of the present invention. However, the present invention is not limited to the embodiments described below.
[0025] (Overall structure) A solid electrolytic capacitor is a passive element that stores and discharges electric charge through capacitance caused by the dielectric polarization effect of a dielectric film. A solid electrolytic capacitor comprises a capacitor element, which includes an anode foil, a cathode, and an electrolyte. A dielectric film is formed on the surface of the anode foil. The electrolyte is a solid electrolyte layer containing a conductive polymer. The solid electrolyte layer adheres closely to the surface of the anode foil and is interposed between the dielectric film of the anode foil and the cathode. This solid electrolyte layer functions as a true cathode by adhering closely to the dielectric film of the anode foil.
[0026] Solid electrolytic capacitors may also be of the so-called hybrid type, which uses both a solid electrolyte layer and an electrolyte solution. That is, hybrid-type solid electrolytic capacitors have an electrolyte solution in addition to a solid electrolyte layer. The electrolyte solution is impregnated into the voids of the capacitor element in which the solid electrolyte layer is formed.
[0027] A separator may be interposed between the anode foil and the cathode body. The separator holds the solid electrolyte layer. The separator also prevents a short circuit between the anode foil and the cathode body. If the solid electrolyte layer maintains its shape on its own, holds the electrolyte, and isolates the anode foil and the cathode body, the separator can be omitted from the configuration of the solid electrolytic capacitor.
[0028] Solid electrolytic capacitors are classified into, for example, multilayer, wound, and planar types. In the multilayer type, the anode foil and cathode body are stacked alternately with a separator in between. In the wound type, the anode foil and cathode body are superimposed with a separator in between and then wound. In the planar type, the solid electrolyte layer and cathode body are stacked on the anode foil.
[0029] In such a solid electrolytic capacitor, anode leads are connected to the anode foil and cathode leads are connected to the cathode body, and these leads are drawn out from the capacitor element. The capacitor element is housed in a case and sealed with a sealing body. The anode leads and cathode leads are electrically and mechanically connected to the anode foil and cathode body by stitch connections, cold welding, ultrasonic welding, or laser welding.
[0030] Solid electrolytic capacitors are electrically connected to the circuit via anode and cathode leads. By conducting electricity with the circuit, the solid electrolytic capacitor becomes a passive element that stores and discharges charge by obtaining capacitance through the dielectric polarization effect of the dielectric film. Various filter circuits can be used as the circuit. Examples of filter circuits include low-pass filters, high-pass filters, band-pass filters, and ripple filters, also known as smoothing circuits.
[0031] (Anode foil) The anode foil is the electrode foil on the anode side, made from a valve metal. Valve metals include aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. The purity of the anode foil should preferably be 99.9% or higher, although it may contain impurities such as silicon, iron, copper, magnesium, and zinc.
[0032] The anode foil may be formed by stretching a valve metal, or by sintering a powder of a valve metal. Furthermore, the anode foil may be formed by laminating the same or different types of valve metal powder onto the surface of a stretched valve metal substrate by sintering or vapor deposition. In wound-type solid electrolytic capacitors, the anode foil has a long, strip-like shape, while in laminated-type and flat-plate-type solid electrolytic capacitors, the anode foil is flat.
[0033] An expanding layer is formed on one or both sides of the anode foil. The expanding layer is a surface layer that has been treated to increase its surface area compared to the projected area perpendicular to the foil surface. The expanding layer is an etched layer formed by etching the foil body, a sintered layer formed by sintering valve metal powder, or a vapor-deposited layer formed by depositing valve metal particles onto the foil. In other words, the expanding layer has a porous structure and consists of tunnel-shaped pits, sponge-like pits, or densely packed powder or voids between particles.
[0034] Tunnel-shaped etching pits are holes carved in the direction of the foil thickness. These tunnel-shaped etching pits are typically formed by passing a direct current through an acidic aqueous solution containing halogen ions, such as hydrochloric acid. The tunnel-shaped etching pits are further expanded by passing a direct current through an acidic aqueous solution containing nitric acid, for example. Sponge-like etching pits cause the expanded layer to become a sponge-like layer with a series of fine voids. These sponge-like etching pits are formed by passing an alternating current through an acidic aqueous solution containing halogen ions, such as hydrochloric acid.
[0035] The sintered layer is produced by pasteuring powder of the same or different valve metal as the foil body with a binder and solvent, coating and drying it on the foil body, and then heating and sintering it in a vacuum or reducing atmosphere. The vapor-deposited layer is produced, for example, by resistance heating vapor deposition or electron beam heating vapor deposition. This vapor-deposited layer is formed by heating the same or different valve metal as the foil body with resistance heat or electron beam energy to evaporate it, and depositing the vapor of valve metal particles onto the surface of the foil body.
[0036] The dielectric film is formed on one or both sides of the anode foil on which the expanding layer is formed. If an expanding layer is formed, the dielectric film is formed on the surface of the expanding layer, following the irregularities of the expanding layer. Typically, the dielectric film is an oxide film formed on the surface of the anode foil, and if the anode foil is made of aluminum, it is an aluminum oxide layer formed by oxidizing the surface of the expanding layer.
[0037] In the chemical conversion treatment for forming a dielectric film, a voltage is applied to the anode foil in the conversion solution to achieve a desired dielectric strength. Furthermore, in the chemical conversion treatment for forming a dielectric film, it is preferable to form a dielectric film with a thickness of 0.9 to 1.5 nm in order to obtain a dielectric strength of 1 V. The conversion solution is a halogen ion-free solution, such as a phosphoric acid-based conversion solution such as ammonium dihydrogen phosphate, a boric acid-based conversion solution such as ammonium borate, or an adipic acid-based conversion solution such as ammonium adipate.
[0038] This dielectric film has a dielectric strength of 300V or higher. In other words, the dielectric film is formed by applying a voltage of 300V or higher during the chemical conversion process. Also, in other words, the dielectric film has a thickness of 270nm or more, or 450nm or more. Solid electrolytic capacitors having this dielectric film with a dielectric strength of 300V or higher are expected to be subjected to a high voltage during use, which is calculated by adding a safety factor to this dielectric strength.
[0039] Furthermore, in chemical conversion treatments that form high-voltage dielectric films, voids may occur within the dielectric film. These voids may be repaired by depolarization treatment. Depolarization treatments include heat treatment, treatment with an acidic solution, treatment with an alkaline solution, treatment with pure water, or a combination of these. In heat treatment, for example, exposure to a temperature environment of 450°C or higher in the atmosphere opens isolated voids within the dielectric film. Examples of acidic and alkaline solutions include phosphoric acid solution, sulfuric acid solution, nitric acid solution, sodium hydroxide solution, potassium hydroxide solution, ammonia solution, or pure water at 60°C or higher. In depolarization treatment, the dielectric film expands, gases within the dielectric film expand, or the layers of the dielectric film chemically dissolve, creating pathways to the voids and opening them. As a result, the chemical conversion solution can easily penetrate the voids, and the voids can be repaired by further chemical conversion treatment.
[0040] (Cathole body) The cathode body is an electrode foil on the cathode side made of a valve metal. The purity of the valve metal is preferably 99% or higher with respect to the cathode body. The cathode body may have a widening layer formed on it, similar to the anode foil, or a plain foil without a widening layer may be used as the cathode body. The cathode body may have a thin oxide film of about 1 to 10 Vfs formed by a native oxide film or a chemical conversion treatment. The native oxide film is formed when the cathode body reacts with oxygen in the air.
[0041] Furthermore, the cathode body may be provided with a conductive layer. The conductive layer is laminated on the cathode foil. The conductive layer may mainly contain inorganic materials or inorganic compounds. Examples of inorganic materials or inorganic compounds include titanium, zirconium, tantalum, niobium, nitrides or carbides thereof, aluminum carbide, carbon materials, and composites or mixtures thereof. Specifically, examples include a carbon layer which is a conductive layer of carbon material, a conductive layer of titanium nitride, a conductive layer of titanium carbide, a conductive layer which is a mixture of titanium and carbon material, and a conductive layer which is a composite of aluminum carbide (Al4C3) and titanium oxide (TiO2).
[0042] The conductive layer containing carbon material, i.e., the carbon layer, contains graphite, carbon black, or a mixture thereof as the carbon material. Examples of graphite include natural graphite, artificial graphite, and graphitized Ketjenblack. Examples of carbon black include Ketjenblack, acetylene black, channel black, and thermal black. In addition, the carbon layer may contain activated carbon, carbon nanohorns, or fibrous carbon as the carbon material. Activated carbon is made from natural plant tissues such as coconut shells, synthetic resins such as phenol, and fossil fuels such as coal, coke, and pitch. Examples of fibrous carbon include carbon nanotubes (hereinafter referred to as CNTs) and carbon nanofibers (hereinafter referred to as CNFs). Activated carbon and fibrous carbon are preferred because their pi electrons are delocalized and they have a large specific surface area.
[0043] In the case of a flat-plate electrolytic capacitor, the cathode body may be a laminate of a metal layer and a carbon layer. The carbon layer of the cathode body is positioned toward the anode foil. The carbon layer is formed by making it into a paste, coating it onto the solid electrolyte layer after it has been formed on the anode foil, and then curing it by heating. The metal layer is, for example, a silver layer, and the metal layer is formed by making it into a paste, coating it on top of the carbon layer, and then curing it by heating.
[0044] (conductive polymer) Conductive polymers are either self-doped conjugated polymers doped with intramolecular dopants, or conjugated polymers doped with external dopant molecules. Conjugated polymers are obtained by chemical oxidation polymerization or electrolytic oxidation polymerization of monomers or derivatives thereof having π-conjugated double bonds. Dopants or external dopant molecules are acceptors that readily accept electrons into the conjugated polymer, or donors that readily donate electrons, thereby enabling the conductive polymer to exhibit high conductivity.
[0045] This conductive polymer can be any known polymer without particular limitation, as long as it contains a sulfur atom in the molecular structure of the dopant, conjugated polymer, or both. Examples of conjugated polymers include polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, and polythiophenevinylene. These conjugated polymers may be used individually, in combination of two or more types, or as copolymers of two or more monomers.
[0046] Among the above-mentioned conjugated polymers, conjugated polymers formed by polymerizing thiophene or its derivatives are preferred, and conjugated polymers formed by polymerizing 3,4-ethylenedioxythiophene (i.e., 2,3-dihydrothieno[3,4-b][1,4]dioxin), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, or derivatives thereof are preferred. As the thiophene derivative, compounds selected from thiophenes having substituents at the 3rd and 4th positions are preferred, and the substituents at the 3rd and 4th positions of the thiophene ring may form a ring together with the carbon atoms at the 3rd and 4th positions. The number of carbon atoms in the alkyl or alkoxy group is suitable to be 1 to 16.
[0047] In particular, a polymer of 3,4-ethylenedioxythiophene called EDOT, i.e., poly(3,4-ethylenedioxythiophene) called PEDOT, is preferred. Furthermore, substituents may be added to 3,4-ethylenedioxythiophene. For example, alkylated ethylenedioxythiophene, in which an alkyl group having 1 to 5 carbon atoms is added as a substituent, may be used. Examples of alkylated ethylenedioxythiophene include methylated ethylenedioxythiophene (i.e., 2-methyl-2,3-dihydrothieno[3,4-b][1,4]dioxin), ethylated ethylenedioxythiophene (i.e., 2-ethyl-2,3-dihydrothieno[3,4-b][1,4]dioxin), and butylated ethylenedioxythiophene (i.e., 2-butyl-2,3-dihydrothieno[3,4-b][1,4]dioxin).
[0048] Dopants can be any known substance without particular limitation. Dopants may be used alone or in combination of two or more. Polymers or monomers may also be used. Examples of dopants include polyanions, inorganic acids such as boric acid, nitric acid, and phosphoric acid, and organic acids such as acetic acid, oxalic acid, citric acid, tartaric acid, squalaneic acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalateborate acid, sulfonylimide acid, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, and butylnaphthalenesulfonic acid.
[0049] Polyanions include, for example, substituted or unsubstituted polyalkylenes, substituted or unsubstituted polyalkenes, substituted or unsubstituted polyimides, substituted or unsubstituted polyamides, and substituted or unsubstituted polyesters, which are polymers consisting only of structural units having anionic groups, or polymers consisting of structural units having anionic groups and structural units not having anionic groups. Specifically, examples of polyanions include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacrylate sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, polymethacrylate, and polymaleic acid.
[0050] Examples of conductive polymers include poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid, and hereafter this conductive polymer will be referred to as PEDOT:PSS.
[0051] Here, Figure 1 is a model diagram showing a region within the anode foil, and is an enlarged view of a portion of the anode foil. As shown in Figure 1, the plane 10S extending in a direction perpendicular to the thickness direction of the anode foil has a foil width 10W in the short-side direction. Starting from the edge 10e1 in the short-side direction, the area extending to the opposite edge 10e2, which is 13% of the foil width 10W, is called the edge region 10A. The edge regions 10A are set on all four sides along each edge of the anode foil. The area on the plane 10S excluding the four edge regions 10A is called the foil surface region 10B.
[0052] The conductive polymer is attached in such a way that the sulfur intensity ratio R per unit area attached to the edge region 10A of the anode foil is 1.92 or less compared to the sulfur per unit area attached to the foil surface region 10B other than the edge region 10A.
[0053] The intensity is measured by EDS elemental analysis using a scanning electron microscope (JEOL Ltd., JCM-7000) and standardized by the intensity of the valve metal used in the anode foil. When measuring the sulfur intensity, the wavelength energy is set to 2.31 keV, and the number of photons detected per unit area is taken as the sulfur intensity measurement. When measuring the valve metal intensity, if the valve metal is aluminum, the wavelength energy is set to 1.48 keV, and the number of photons detected per unit area is taken as the valve metal intensity measurement. The sulfur intensity is taken as the divided value obtained by dividing the sulfur intensity measurement by the valve metal intensity measurement.
[0054] The sulfur intensity ratio R is given by the following equation (1), which is the value obtained by dividing the sulfur intensity in the edge region 10A by the sulfur intensity in the foil surface region 10B. The adhesion position and amount of the conductive polymer are adjusted so that this sulfur intensity ratio R becomes R ≤ 1.92, as shown in the following equation (2).
[0055] (Formula 1) TIFF2026165968000002.tif11150
[0056] (Formula 2) TIFF2026165968000003.tif11150
[0057] In equation (1) above, SvA is the measured sulfur intensity per unit area within the edge region 10A, and SvB is the measured sulfur intensity per unit area within the foil surface region 10B. Also, in equation (1), AvA is the measured aluminum intensity per unit area within the edge region 10A, and AvB is the measured aluminum intensity per unit area within the foil surface region 10B. Although aluminum is used as an example here, AvA and AvB are the measured intensity of the valve metal used in the anode foil, respectively.
[0058] When the sulfur intensity ratio R is 1.92 or less, the voltage rating of the solid electrolytic capacitor improves. While not limited to this hypothesis, the mechanism by which the voltage rating of the solid electrolytic capacitor improves is presumed to be as follows.
[0059] First, the sulfur intensity ratio R represents the relative amount of conductive polymer adhering to the edge region 10A of the anode foil. That is, the sulfur intensity ratio R represents the amount of conductive polymer adhering to the edge region 10A relative to the amount of conductive polymer adhering to the foil surface region 10B of the anode foil. The edge region 10A acts as an entry point for the conductive polymer to penetrate into the anode foil, and due to the coffee ring effect, when conductive polymer is attached to the anode foil, the amount of conductive polymer adhering to the edge region 10A increases.
[0060] Defects in the dielectric film, such as cracks and dissolution, can cause leakage current at the affected areas. When conductive polymers are incorporated into the path through which the leakage current flows, an increase in the amount of conductive polymers lowers the circuit's resistance, resulting in a larger leakage current. The edge region 10A has a large amount of conductive polymer attached, making it easier for a large localized current to flow in the edge region 10A of the anode foil. Heat generated by overcurrent accelerates the deterioration of the dielectric film, leading to a decrease in the withstand voltage of the solid electrolytic capacitor.
[0061] However, if the amount of conductive polymer adhering to the edge region 1A can be reduced so that the sulfur intensity ratio R is 1.92 or less, the leakage current generated in the edge region 10A will begin to decrease, the dielectric film in the edge region 10A will begin to deteriorate less, and the voltage withstand capability of the solid electrolytic capacitor will begin to improve.
[0062] More preferably, the sulfur intensity ratio R is 1.71 or less. If the amount of conductive polymer adhering to the edge region 10A can be reduced so that the sulfur intensity ratio R is 1.71 or less, the dielectric strength of the solid electrolytic capacitor will be greatly improved.
[0063] As a method for attaching the conductive polymer to the anode foil, a method is adopted in which the edge region 10A serves as the inlet for penetration of the conductive polymer. For example, the conductive polymer can be formed using a conductive polymer liquid. The conductive polymer liquid is a dispersion or solution in which the conductive polymer is dispersed or dissolved.
[0064] Winded or laminated capacitor elements are impregnated with a conductive polymer solution by immersing them in the solution. Alternatively, the conductive polymer solution is applied to the anode foil. The impregnation or application of the conductive polymer solution may be repeated multiple times with drying intervals in between. The inside of the winding body may be depressurized, or in addition, the conductive polymer solution may be pressurized while impregnating the capacitor elements with the conductive polymer solution.
[0065] Methods for adjusting the sulfur intensity ratio R include, for example, reducing the adhesion of the conductive polymer to the edge region 10A, transferring some or all of the conductive polymer attached to the edge region 10A to the foil surface region 10B, and reducing some or all of the conductive polymer in the edge region 10A.
[0066] One method to reduce adhesion is to apply a resin coating or a water-repellent coating to the edge region 10A before impregnating the capacitor element with a conductive polymer solution. Another method to transfer the conductive polymer is to rotate the capacitor element in a centrifuge after applying the conductive polymer. A method to reduce the amount of conductive polymer is to wash it off from the edge region 10A using an organic solvent or water. Alternatively, a method to reduce the amount of conductive polymer is to burn off the conductive polymer in the edge region 10A by laser irradiation.
[0067] (solid electrolyte layer) In addition to conductive polymers, the solid electrolyte layer may also contain compounds having hydroxyl groups and a boiling point of 150°C or higher. Compounds having hydroxyl groups cause changes in the higher-order structure of the conductive polymer, resulting in reduced ESR and improved voltage withstand capability of the solid electrolytic capacitor. If the boiling point is 150°C or higher, the compound will remain in the solid electrolyte layer even after drying by volatilizing the solvent of the conductive polymer liquid after impregnation or coating of the capacitor element, thus easily forming the solid electrolyte layer.
[0068] Compounds having a hydroxyl group and a boiling point of 150°C or higher include ethylene glycol, diethylene glycol, triethylene glycol, polyoxyethylene glycol, glycerin, and polyglycerin. The solid electrolyte layer may contain one or more compounds having a hydroxyl group and a boiling point of 150°C or higher.
[0069] (electrolyte) Hybrid solid electrolytic capacitors use an electrolyte in addition to a solid electrolyte layer. The electrolyte is a solution in which a solute is added to a solvent. The solute is an organic acid or its salt, an inorganic acid or its salt, or a composite compound of an organic acid and an inorganic acid or its salt, and is an ionic dissociable salt that dissociates into an anionic component and a cationic component. The solvent is used alone or in combination of two or more types.
[0070] Organic acids that act as anionic components as solutes include carboxylic acids such as oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, resorcinic acid, phloroglucic acid, gallic acid, gentisic acid, protocatechuic acid, pyrocatechuic acid, trimellitic acid, pyromellitic acid, undecanediic acid, dodecanediic acid, tridecanediic acid, t-butyladipic acid, and 11-vinyl-8-octadecenediic acid, as well as phenols and sulfonic acids. Inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Examples of complex compounds of organic and inorganic acids include borodisalicylic acid, borodisuoic acid, borodiglycolic acid, borodimalonic acid, borodisuccinic acid, borodiadipic acid, borodiazelaic acid, borodibenzoic acid, borodimaleic acid, borodilactic acid, borodimalic acid, boroditartaric acid, borodicitric acid, borodiphthalic acid, borodi(2-hydroxy)isobutyric acid, borodiresorcinic acid, borodimethylsalicylic acid, borodinafthoic acid, borodimandelic acid, and borodi(3-hydroxy)propionic acid.
[0071] Cationic components include ammonium, quaternary ammonium, amidinium quaternary, amines, sodium, potassium, etc. Quaternary ammonium includes tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Amidinium quaternary includes ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Amines include primary amines, secondary amines, and tertiary amines. Primary amines include methylamine, ethylamine, propylamine, etc. Secondary amines include dimethylamine, diethylamine, ethylmethylamine, dibutylamine, etc. Tertiary amines include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, ethyldiisopropylamine, etc.
[0072] Furthermore, anions and cations may be added to the electrolyte in the form of ionically dissociable salts, or the acid that forms the anion and the base that forms the cation may be added separately to the electrolyte as solute components. Anions and cations can be used individually or in combination of two or more types.
[0073] The solvent may be either a protic polar solvent or an aprotic polar solvent. Examples of protic polar solvents include monohydric alcohols, polyhydric alcohols, and oxyalcohol compounds. Examples of aprotic polar solvents include sulfones, amides, lactones, cyclic amides, and nitriles.
[0074] Examples of monohydric alcohols include ethanol, propanol, butanol, pentanol, hexanol, cyclobutanol, cyclopentanol, cyclohexanol, and benzyl alcohol. Examples of polyhydric alcohols and oxyalcohol compounds include ethylene glycol, propylene glycol, glycerin, methyl cellosolve, ethyl cellosolve, methoxypropylene glycol, and dimethoxypropanol.
[0075] Examples of sulfones include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, sulfolane, 3-methylsulfolane, and 2,4-dimethylsulfolane. Examples of amides include N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, N,N-diethylacetamide, and hexamethylphosphoric amide. Examples of lactones and cyclic amides include γ-butyrolactone, γ-valerolactone, δ-valerolactone, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, and isobutylene carbonate. Examples of nitriles include acetonitrile, 3-methoxypropionitrile, and glutaronitrile.
[0076] Furthermore, other additives can be added to the electrolyte. Examples of additives include complex compounds of boric acid and polysaccharides (such as mannitol and sorbitol), complex compounds of boric acid and polyhydric alcohols, boric acid esters, nitro compounds, phosphate esters, and colloidal silica. These may be used individually or in combination of two or more. Nitro compounds suppress the generation of hydrogen gas in solid electrolytic capacitors. Examples of nitro compounds include o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, p-nitrobenzyl alcohol, and m-nitroacetophenone.
[0077] Furthermore, the electrolyte may contain a polymer component as a voltage-breaking agent for solid electrolytic capacitors, in a proportion of 20 wt% or more of the total electrolyte volume. The polymer component is preferably a polyol or a derivative thereof having one or more alkylene oxide groups attached and a molecular weight of 600 or more.
[0078] Polyols or derivatives thereof to which alkylene oxide groups are added include polyethylene glycol, polyethylene glycol glyceryl ether, polyethylene glycol diglyceryl ether, polyethylene glycol triglyceryl ether, polypropylene glycol, polypropylene glycol glyceryl ether, polypropylene glycol diglyceryl ether, polypropylene glycol triglyceryl ether, polyoxyethylene glycerin, polyoxypropylene glycerin, glycols containing ethylene oxide and propylene oxide, and glycerins containing ethylene oxide and propylene oxide.
[0079] (Separator) Examples of separators include cellulose and mixed papers such as kraft, Manila hemp, esparto, hemp, and rayon; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and their derivatives; polyamide resins such as polytetrafluoroethylene resins, polyvinylidene fluoride resins, vinylon resins; polyamide resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide resins; polyethylene resins; polypropylene resins; trimethylpentene resins; polyphenylene sulfide resins; acrylic resins; and polyvinyl alcohol resins. These resins can be used individually or in mixtures.
[0080] (Manufacturing method) An example of a manufacturing method for such solid electrolytic capacitors is shown. The manufacturing method includes an anode foil formation step for forming an anode foil, a cathode body formation step for forming a cathode body, an electrolyte layer formation step for forming a solid electrolyte layer, and a packaging step for housing the capacitor elements in a case. In the case of wound-type and multilayer-type solid electrolytic capacitors, an element formation step for forming the capacitor elements is included before the electrolyte layer formation step. In the case of hybrid-type solid electrolytic capacitors, an electrolyte impregnation step for impregnating them with electrolyte is included after the electrolyte layer formation step.
[0081] The order of these processes can be rearranged as freely as possible, and parallel processing is also possible. Furthermore, one process may include multiple sub-processes, some of which may be performed within other processes, or incorporated between one sub-process of one process and the next.
[0082] In the anode foil formation process and the cathode body formation process, in the manufacturing method of wound-type solid electrolytic capacitors, the anode foil and cathode body are processed into long lengths. In the manufacturing method of laminated-type solid electrolytic capacitors, the anode foil and cathode body are processed into wide flat plates. In the manufacturing method of flat-plate-type solid electrolytic capacitors, the anode foil is processed into a flat plate.
[0083] In the anode foil formation process, a widening layer is formed on one or both sides of the anode foil, and a dielectric film is formed on the widening layer by a chemical conversion treatment. In the cathode body formation process, a widening layer is formed on one or both sides of the cathode body as needed, and an oxide film is formed on the surface. The anode leads and cathode leads are electrically and mechanically connected to the anode foil and cathode body.
[0084] In the element formation process, a long anode foil and cathode body are wound with a separator in between to create a cylindrical wound body. The separator is overlapped so that one end extends beyond one end of the anode foil and cathode body. The core of the wound body is created by starting to wind the protruding separator first so that the core of the wound body follows the short sides of the anode foil and cathode body. Then, using this winding core as the winding axis, the long sides of the anode foil and cathode body are rounded to create the wound body. In the element formation process, flat anode foils and cathode bodies are stacked alternately with a separator in between to create a laminate.
[0085] A repair and chemical conversion process may be provided to repair the exposed base metal portion of the valve-acting metal when the anode foil and cathode body are cut to a desired width after winding and lamination, as well as any defects in the anode foil and cathode body caused by physical stress such as winding.
[0086] In the repair chemical conversion process, the wound body is immersed in a conversion solution and a voltage is applied. The conversion solution can be a phosphoric acid-based solution such as ammonium dihydrogen phosphate, a boric acid-based solution such as ammonium borate, an adipic acid-based solution such as ammonium adipate, or a solution made by mixing boric acid and dicarboxylic acids such as citric acid. The voltage is preferably, for example, 0.1 to 1.2 times the conversion voltage. Furthermore, as a method of applying the voltage during repair chemical conversion, a method of applying a constant voltage from the start of repair chemical conversion, or a method of gradually increasing the applied voltage at regular intervals can be appropriately selected.
[0087] In the electrolyte layer formation process, a solid electrolyte layer is formed between the anode foil and the cathode body, for example, using a conductive polymer solution. The dispersion medium or solvent for the conductive polymer solution can be any solution in which the particles or powder of the conductive polymer are dispersed or dissolved. The dispersion medium or solvent for the conductive polymer solution is water, or a mixture of water and an organic solvent. Suitable examples of organic solvents include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, nitrile compounds, and sulfones.
[0088] Examples of polar solvents include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. Examples of alcohols include methanol, ethanol, propanol, butanol, ethylene glycol, glycerin, and polyglycerin. Examples of esters include ethyl acetate, propyl acetate, and butyl acetate. Examples of hydrocarbons include hexane, heptane, benzene, toluene, and xylene. Examples of carbonate compounds include ethylene carbonate and propylene carbonate. Examples of ether compounds include dioxane and diethyl ether. Examples of linear ethers include ethylene glycol dialkyl ether, propylene glycol dialkyl ether, polyethylene glycol dialkyl ether, and polypropylene glycol dialkyl ether. Examples of heterocyclic compounds include 3-methyl-2-oxazolidinone. Examples of nitrile compounds include acetonitrile, glutalodinitrile, methoxyacetonitrile, propionitrile, and benzonitrile. Examples of sulfone compounds include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, sulfolane, 3-methylsulfolane, and 2,4-dimethylsulfolane.
[0089] Compounds containing a hydroxyl group and having a boiling point of 150°C or higher are added to this conductive polymer solution. pH adjusters and various additives may be added to the conductive polymer solution as needed.
[0090] pH adjusters neutralize dopants to improve the acidity of the conductive polymer solution, preventing the anode foil, cathode body, and separator from dissolving. Examples of pH adjusters include ammonia, water-soluble alkylamines such as ethylamine and diethylamine, water-soluble arylamines such as aniline and benzylamine, and water-soluble heterocyclic amines such as pyridine and imidazole. Other examples of pH adjusters include alkali metal or alkaline earth metal hydroxides such as sodium hydroxide and calcium hydroxide, alkali metal or alkaline earth metal carbonates such as sodium carbonate and calcium carbonate, and alkali metal or alkaline earth metal alkoxides such as sodium methoxide and calcium methoxide.
[0091] Examples of additives include organic binders, surfactants, dispersants, defoamers, coupling agents, antioxidants, and UV absorbers. Examples of organic binders include polyvinyl alcohol, methyl methacrylate, and hydroxypropyl methylcellulose. Examples of surfactants include sorbitan oleate, polyoxyethylene sorbitan oleate, and alkylphenol polyoxyethylene ether. Examples of dispersants include polyvinylpyrrolidone, carboxymethylcellulose, and polyoxyethylene. Examples of defoamers include silicone oil, polyglycerin laurate, and polyglycerin polyphosphate. Examples of coupling agents include silane coupling agents, polyimide coupling agents, and titanate esters. Examples of antioxidants include hydroquinone, methylhydroquinone, and 1,4-dihydroxybenzene. Examples of UV absorbers include benzophenone, octocrylene, and avobenzone.
[0092] If the process includes an electrolyte impregnation step, the capacitor element is immersed in the electrolyte to impregnate the voids within the capacitor element. To impregnate even finer voids with the electrolyte, depressurization or pressurization may be performed as needed. The electrolyte impregnation step may be repeated multiple times. For example, the inside of the capacitor element may be depressurized, and the electrolyte may be injected into the capacitor element while pressurizing the electrolyte.
[0093] In the packaging process, the capacitor elements are housed in an outer case with a closed bottom at one end and an open end at the other. The opening of the outer case is sealed with a sealing body. The sealing body is made of an elastic insulator such as a rubber sheet, or a laminate of a rigid substrate insulating plate such as a synthetic resin sheet and an elastic insulator, and is crimped from the outside of the outer case. After sealing the capacitor elements in the outer case, the electrolytic capacitor is manufactured after undergoing an aging process. In the aging process, a DC voltage is applied to the electrolytic capacitor to repair defects in the dielectric oxide film layer and other areas, and to insulate conductive polymers present in the defective areas of the dielectric film, thereby improving the reliability of the electrolytic capacitor.
[0094] (Stacked type) In a flat-plate solid electrolytic capacitor, the process proceeds from the anode foil formation step to the electrolyte layer formation step, followed by the cathode body formation step. Before the electrolyte layer formation step, an insulating resist layer is printed and dried, including the region that will later become the anode terminal, but excluding the region that will become the anode. In other words, the insulating resist layer is printed so that the electrolyte layer is not formed in the region that will become the anode terminal.
[0095] After printing the insulating resist layer, the process moves to the electrolyte layer formation step, where the anode foil is immersed in a conductive polymer solution, or the conductive polymer solution is applied to the anode foil by drop or spray coating, thereby depositing the conductive polymer to cover the dielectric film. Unnecessary solvents from the conductive polymer solution are removed by drying.
[0096] Next, the process moves to the cathode formation step, where carbon paste is printed onto the electrolyte layer using a screen printing machine or the like and then dried. This drying process forms a carbon layer on the electrolyte layer. Furthermore, a metal paste such as silver paste is printed onto the carbon layer and dried. After this drying process, a silver layer is formed on the carbon layer.
[0097] After forming the cathode, the insulating resist layer is removed. The insulating resist layer may be removed by laser irradiation or mechanical removal using a jig. The exposed portion is then plated to complete the anode terminal. For flat-plate capacitor elements, the outer casing can be omitted, or the element can be covered with, for example, a laminate film. Alternatively, the capacitor element may be sealed by molding, dip coating, or printing with a resin such as a heat-resistant resin or insulating resin.
[0098] (circuit) Solid electrolytic capacitors are suitable for various filter circuits. Examples of filter circuits include low-pass filters, high-pass filters, band-pass filters, and ripple filters, also known as smoothing circuits.
[0099] Figure 2 is a circuit diagram showing an example of a smoothing circuit equipped with this solid electrolytic capacitor. This smoothing circuit 1 includes a diode 2, a solid electrolytic capacitor 3, and an inrush current limiting circuit 4. Diode 2 is connected in series with the circuit and allows the rectified input voltage Vin to pass through while preventing reverse connection. Solid electrolytic capacitor 3 is placed after diode 2 and connected in parallel with the circuit to smooth the rectified input voltage Vin.
[0100] The inrush current limiting circuit 4 is inserted in series between the diode 2 and the solid electrolytic capacitor 3. The inrush current limiting circuit 4 includes a resistor 41 and a switch 42 connected in parallel. The resistor 41 limits the peak value of the inrush current input to the solid electrolytic capacitor 3. The switch 42 opens when an inrush current occurs and closes after the solid electrolytic capacitor 3 has been charged, short-circuiting the resistor 41 and thereby reducing power loss.
[0101] In this smoothing circuit 1, by incorporating a solid electrolytic capacitor 3 that comprises an anode foil having a dielectric film with a voltage withstand voltage of 300V or more, and a conductive polymer containing sulfur in its molecular structure, and in which the sulfur intensity ratio R is 1.92 or less relative to the amount of sulfur per unit area attached to the foil surface region 10B other than the edge region 10A, this high-voltage solid electrolytic capacitor makes it possible to reduce the ripple voltage in the high-frequency band and reduce the number of capacitors. Reducing the number of capacitors makes it possible to miniaturize the entire circuit and realize a circuit with good volume efficiency.
[0102] Figure 3 is a circuit diagram showing an example of a filter circuit equipped with this solid electrolytic capacitor. The filter circuit 5 shown in Figure 3 includes a solid electrolytic capacitor 3 and an inrush current limiting circuit 4. The solid electrolytic capacitor 3 is connected in parallel to the circuit, and the inrush current limiting circuit 4 is connected in series to the circuit before the solid electrolytic capacitor 3. The inrush current limiting circuit 4 includes a resistor 41 and a switch 42 connected in parallel.
[0103] This filter circuit 5 incorporates a solid electrolytic capacitor 3 that has an anode foil with a dielectric film with a voltage rating of 300V or higher, and a conductive polymer containing sulfur in its molecular structure, where the sulfur intensity ratio R is 1.92 or less relative to the amount of sulfur per unit area attached to the foil surface region 10B, excluding the edge region 10A. This high-voltage solid electrolytic capacitor enables a reduction in ripple voltage in the high-frequency band, thereby reducing the number of capacitors. Reducing the number of capacitors allows for miniaturization of the entire circuit, resulting in a circuit with good volume efficiency. [Examples]
[0104] The solid electrolytic capacitor will be described in more detail below based on the following examples. However, the present invention is not limited to the following examples.
[0105] (Examples 1 to 4) Solid electrolytic capacitors of Examples 1 to 4 and Comparative Examples 1 and 2 were fabricated. The difference between these solid electrolytic capacitors lies in the ratio R of sulfur per unit area attached to the edge region 10A (hereinafter simply referred to as the sulfur intensity ratio R) to the sulfur per unit area attached to the foil surface region 10B of the anode foil. The other components of the solid electrolytic capacitors of Examples 1 to 4 and Comparative Examples 1 and 2 are identical.
[0106] The anode foil was formed from a long, stretched strip of aluminum foil. In the anode foil formation process, the anode foil was enlarged by etching, and a dielectric film was formed on the surface of the anode foil by chemical conversion treatment. In the enlargement treatment, the anode foil was immersed in an aqueous hydrochloric acid solution, and a DC current was passed through the anode foil in the aqueous hydrochloric acid solution to form an enlarged layer consisting of tunnel-shaped etching pits. In the chemical conversion treatment of the anode foil, it was immersed in an aqueous boric acid (H3BO3) solution with a concentration of 0.5 mol / L at a liquid temperature of 90°C, and treated with a current of 50 mA / cm². 2 A constant current was passed through while a voltage was applied. The voltage was applied until the chemical voltage reached 660V.
[0107] The cathode body was a long, stretched strip of aluminum foil. No surface expansion or chemical treatment was performed on the cathode body. Lead wires were connected to both the anode foil and the cathode body, and the anode foil and cathode body were wound together with a cellulose-based separator in between. A current of 10 mA / cm² was applied to the wound body immersed in an ammonium borate aqueous solution. 2 The repair process was carried out by applying a low voltage until it reached 550V. After the repair process, the wound material was exposed to a 60°C temperature environment for drying.
[0108] Next, a solid electrolyte layer was formed on the wound body in the electrolyte formation process. Conductive polymer and ethylene glycol were left as residues in the solid electrolyte layer. Specifically, the wound body was immersed in a conductive polymer solution, and the components of the conductive polymer solution containing conductive polymer and ethylene glycol were deposited on the dielectric film of the anode foil, the cathode body, and the separator. Then, the wound body was exposed to a temperature environment of 110°C for 2 hours to allow the solvent to evaporate.
[0109] The conductive polymer solution contained dispersed poly(3,4-ethylenedioxythiophene) (PEDOT) particles doped with polyethylene sulfonic acid (PSS) as the conductive polymer. The conductive polymer was dispersed using an ultrasonic homogenizer. The dispersion medium for the conductive polymer solution was a mixture of 90 wt% water and 10 wt% ethylene glycol. The conductive polymer was dispersed in the conductive polymer solution to a concentration of 1.5 wt%. 2 wt% sorbitol was added to the conductive polymer solution relative to the total volume of the conductive polymer solution.
[0110] In the electrolyte layer formation process, an adjustment process was performed to wash the wound body impregnated with conductive polymer solution, thereby adjusting the sulfur intensity ratio R. Comparative Example 1 was left unwashed. In Comparative Example 2 and Examples 1 to 4, the end region 10A was immersed in ethylene glycol. The immersion time for each was varied according to the desired sulfur intensity ratio R.
[0111] In the electrolyte impregnation process, the capacitor element with a solid electrolyte layer was impregnated with an electrolyte. The electrolyte consisted of ethylene glycol, an alkylene oxide-added glycerol derivative, and ammonium azelaate. Ethylene glycol was added to account for 80 wt% of the solvent, and the alkylene oxide-added glycerol derivative was added to account for 20 wt% of the solvent. The alkylene oxide-added glycerol derivative is formed by adding a polymer of alkylene oxide to the positions of two hydroxyl groups of glycerol, and has a molecular weight of 3000. The concentration of ammonium azelaate was 3.4 wt%.
[0112] The capacitor element was inserted into a bottomed cylindrical case, a sealing body was attached to the open end, and the case was sealed by crimping. Then, the solid electrolytic capacitor was subjected to an aging treatment by applying a voltage. The solid electrolytic capacitor was a wound type with a diameter of 16 mm and a height of 35 mm, and its rated capacitance was 39 μF.
[0113] The sulfur intensity ratio R of the anode foil in each solid electrolytic capacitor was measured as follows. The observation area was defined as the edge region 10A and the foil surface region 10B, ranging from 5 mm to 20 mm along the edge 10e1 from the anode lead 11 as shown in Figure 1. Three measurement points were further defined within this observation area. Elemental analysis of each measurement point was performed using a scanning electron microscope (JEOL Ltd., JCM-7000). The sulfur intensity and aluminum intensity in the edge region 10A and the foil surface region 10B were taken as the average value obtained from the three measurement points.
[0114] As a result, the sulfur intensity ratio R for Comparative Example 1 was 2.23, the sulfur intensity ratio R for Comparative Example 2 was 1.94, the sulfur intensity ratio R for Example 1 was 1.92, the sulfur intensity ratio R for Example 2 was 1.76, the sulfur intensity ratio R for Example 3 was 1.71, and the sulfur intensity ratio R for Example 4 was 1.63.
[0115] The dielectric strength of the anode foil dielectric film of each solid electrolytic capacitor was measured as follows. First, the solid electrolytic capacitor was disassembled and the anode foil was removed. The solid electrolyte layer was burned off by treating it in an electric furnace at 400°C in an atmospheric environment for more than 5 hours. The anode foil from which the solid electrolyte layer had been burned off was immersed in a boric acid aqueous solution with a concentration of 22 g / L at a liquid temperature of 85°C, and a voltage of 2 mA / 5 cm was applied. 2 A constant current was applied. While the constant current was applied, the voltage was measured, and the point at which the voltage changed over time was defined as the dielectric breakdown voltage of the dielectric film.
[0116] Let's further explain the point where the voltage change over time. Figure 4 is a graph showing the voltage change over time, with the horizontal axis representing elapsed time and the vertical axis representing voltage. An extrapolation line A is drawn as an approximation line from the start of voltage application to the rising portion. An extrapolation line B is drawn as an approximation line to the portion where the voltage rises steadily and gradually after the slope of the graph changes. Extrapolation lines A and B were calculated using the least squares method. The intersection point C of these extrapolation lines A and B was defined as the dielectric breakdown voltage of the anode foil's dielectric film.
[0117] As a result, the dielectric film of the anode foil in the solid electrolytic capacitors of Examples 1 to 4 and Comparative Examples 1 and 2 had a dielectric strength of 660V.
[0118] (Withstand voltage test) The withstand voltage of the solid electrolytic capacitors in Examples 1 to 4 and Comparative Examples 1 and 2 was measured. The method for measuring the withstand voltage was as follows: The solid electrolytic capacitors were left in a 105°C environment for 1 hour, and then the withstand voltage was measured. The ambient temperature at the time of the withstand voltage measurement was 105°C. The starting voltage was 100V. The voltage was increased from 100V in increments of 1V over 10 seconds. The current-voltage rise curve was examined, and the voltage (V) when a current of 2mA flowed through the solid electrolytic capacitor was defined as the withstand voltage.
[0119] The measured dielectric strength of the dielectric film on the anode foil and the sulfur intensity ratio R are both shown in Table 1 below. (Table 1) TIFF2026165968000004.tif71131
[0120] Based on Table 1, a graph was created in Figure 5, where the horizontal axis represents the sulfur intensity ratio R and the vertical axis represents the withstand voltage of the solid electrolytic capacitor. As shown in Table 1 and Figure 5, the solid electrolytic capacitors of Comparative Examples 1 and 2, where the sulfur intensity ratio R is in the range of 2.23 to 1.94, do not show a significant change in withstand voltage. As shown in the graph, the change in withstand voltage is nearly flat within this range of sulfur intensity ratio R.
[0121] However, once the sulfur intensity ratio R reaches 1.92, the withstand voltage improves significantly in proportion to the decrease in the sulfur intensity ratio R. The solid electrolytic capacitors of Examples 1 to 4 exhibit higher withstand voltages compared to Comparative Examples 1 and 2. The solid electrolytic capacitor of Example 3, with a sulfur intensity ratio R of 1.71, shows the highest withstand voltage in the sulfur intensity ratio R range of 1.92 to 1.71, where the efficiency of the withstand voltage improvement is best.
[0122] This confirmed that when the sulfur intensity ratio R per unit area attached to the edge region 10A of the anode foil is 1.92 or less compared to the sulfur per unit area attached to the foil surface region 10B (excluding the foil region 10A), the dielectric strength of the solid electrolytic capacitor improves. Furthermore, it was confirmed that the dielectric strength of the solid electrolytic capacitor is best when this sulfur intensity ratio is 1.71 or less.
[0123] (Examples 5 to 8) Solid electrolytic capacitors of Examples 5 to 8 and Comparative Examples 3 to 8 were fabricated. The solid electrolytic capacitors of Examples 5 to 8 and Comparative Examples 3 to 8 had the same configuration as those of Examples 1 to 4, except for the sulfur intensity ratio R and the dielectric breakdown voltage of the anode foil film, and were fabricated using the same manufacturing method and conditions.
[0124] The dielectric film of the anode foil in Example 5 and Comparative Example 3 had a dielectric breakdown voltage of 660V. The dielectric film of the anode foil in Example 6 and Comparative Example 4 had a dielectric breakdown voltage of 521V. The dielectric film of the anode foil in Example 7 and Comparative Example 5 had a dielectric breakdown voltage of 389V. The dielectric film of the anode foil in Example 8 and Comparative Example 6 had a dielectric breakdown voltage of 302V. The dielectric breakdown voltages of the dielectric films of the anode foil in Examples 5 to 8 and Comparative Examples 3 to 6 all exceeded 300V. In contrast, the dielectric film of the anode foil in Comparative Example 7 and Comparative Example 8 had a dielectric breakdown voltage of 232V.
[0125] In each group, the sulfur intensity ratio R for Examples 5 to 8 and Comparative Example 7 was set to 1.63, which is 1.92 or less. In each group, the sulfur intensity ratio R for Comparative Examples 3 to 6 and Comparative Example 8 was set to 2.23, which is greater than 1.92. In the group with a sulfur intensity ratio R of 2.23, no treatment to adjust the sulfur intensity ratio R was performed after impregnation with the conductive polymer solution. In the group with a sulfur intensity ratio R of 1.63, an adjustment step was placed within the electrolyte layer formation step, and the wound body impregnated with the conductive polymer solution was washed.
[0126] (Withstand voltage test) The withstand voltage of the solid electrolytic capacitors in Examples 5 to 8 and Comparative Examples 3 to 8 was measured. The method for measuring the withstand voltage was the same as in Examples 1 to 4. In each group, the withstand voltage of the solid electrolytic capacitor with a sulfur intensity ratio R of 2.23 that had not undergone the adjustment process was calculated by subtracting it from the withstand voltage of the solid electrolytic capacitor with a sulfur intensity ratio R of 1.92 or less that had undergone the adjustment process, and the improvement value was calculated. The measurement results of the withstand voltage and the improvement value are shown in Table 2 below, for both the withstand voltage of the dielectric film of the anode foil and the sulfur intensity ratio R.
[0127] (Table 2) TIFF2026165968000005.tif111161
[0128] Based on Table 2 above, Figure 6 shows the relationship between the breakdown voltage of the dielectric film on the anode foil and the improvement in the breakdown voltage of the solid electrolytic capacitor. As shown in Table 2 and Figure 6 above, even if the sulfur intensity ratio R is set to 1.92 or less compared to the breakdown voltage of Comparative Example 8, there is no change in the breakdown voltage of Comparative Example 7. On the other hand, improvements were observed in the breakdown voltage of Example 5 compared to Comparative Example 3, the breakdown voltage of Example 6 compared to Comparative Example 4, the breakdown voltage of Example 7 compared to Comparative Example 5, and the breakdown voltage of Example 8 compared to Comparative Example 6.
[0129] The difference between Examples 5 to 8 and Comparative Examples 3 to 6 and Comparative Examples 7 and 8 lies in the dielectric breakdown voltage of the anode foil. When the dielectric breakdown voltage of the anode foil was less than 300V, setting the sulfur intensity ratio R to 1.92 or less did not improve the breakdown voltage of the solid electrolytic capacitor. On the other hand, when the dielectric breakdown voltage of the anode foil was 300V or higher, setting the sulfur intensity ratio R to 1.92 or less improved the breakdown voltage of the solid electrolytic capacitor.
[0130] In other words, it was confirmed that the voltage withstand capability of the solid electrolytic capacitor is improved not only by setting the sulfur intensity ratio R to 1.92 or less, but also by setting the dielectric strength of the anode foil to 300V or more.
[0131] (Examples 9 to 12) Solid electrolytic capacitors of Examples 9 to 12 and Comparative Examples 9 and 10 were fabricated. The solid electrolytic capacitors of Examples 9 to 12 and Comparative Examples 9 and 10 do not contain electrolyte and contain only a conductive polymer as the electrolyte. The dielectric film of the anode foil has a dielectric strength of 660V. The sulfur intensity ratio R of Comparative Example 9 is 2.23, the sulfur intensity ratio R of Comparative Example 10 is 1.94, the sulfur intensity ratio R of Example 9 is 1.92, the sulfur intensity ratio R of Example 10 is 1.76, the sulfur intensity ratio R of Example 11 is 1.71, and the sulfur intensity ratio R of Example 12 is 1.63.
[0132] These solid electrolytic capacitors have the same configuration as Examples 1 to 4, except that the electrolyte impregnation process is omitted and they are unimpregnated with electrolyte, and were manufactured using the same manufacturing method and under the same manufacturing conditions.
[0133] (Withstand voltage test) The withstand voltage of the solid electrolytic capacitors of Examples 9 to 12 and Comparative Examples 9 and 10 was measured. The measurement method and conditions for withstand voltage were the same as those for Examples 1 to 4. The measurement results for withstand voltage, including the withstand voltage of the dielectric film of the anode foil and the sulfur intensity ratio R, are shown in Table 3 below.
[0134] (Table 3) TIFF2026165968000006.tif71131
[0135] Based on Table 3, Figure 7 was created, with the horizontal axis representing the sulfur intensity ratio R and the vertical axis representing the withstand voltage of the solid electrolytic capacitor. As shown in Table 3 and Figure 7, the solid electrolytic capacitors of Comparative Examples 9 and 10, where the sulfur intensity ratio R is in the range of 2.23 to 1.94, do not show a significant change in withstand voltage. As shown in the graph, the change in withstand voltage is nearly flat within this range of sulfur intensity ratio R.
[0136] However, once the sulfur intensity ratio R reaches 1.92, the withstand voltage improves significantly in proportion to the decrease in the sulfur intensity ratio R. The solid electrolytic capacitors of Examples 9 to 12 exhibit higher withstand voltages compared to Comparative Examples 9 and 10. The solid electrolytic capacitor of Example 11, with a sulfur intensity ratio R of 1.71, shows the highest withstand voltage in the sulfur intensity ratio R range of 1.92 to 1.71, where the efficiency of the withstand voltage improvement is best.
[0137] This confirmed that, whether the electrolyte is a combination of conductive polymer and electrolyte solution, or conductive polymer alone, if the dielectric film of the anode foil has a withstand voltage of 300V or more and the sulfur intensity ratio R is 1.92 or less, the withstand voltage of the solid electrolytic capacitor improves.
[0138] (Examples 13 to 16) Hybrid type solid electrolytic capacitors were fabricated in Examples 13 to 16. Examples 13 to 16 differ from the hybrid type solid electrolytic capacitor of Example 1 in the amount of polymer component in the electrolyte. Except for the difference in the amount of polymer component added, the solid electrolytic capacitors of Examples 13 to 16 had the same configuration as Example 1 and were fabricated using the same manufacturing method and conditions.
[0139] In Example 1, an alkylene oxide-added glycerol derivative was added to the electrolyte as a polymer component to occupy 20 wt% of the solvent. In contrast, in Example 13, the same polymer component as in Example 1 was added to the electrolyte to occupy 15 wt% of the solvent. In Example 14, the same polymer component as in Example 1 was added to the electrolyte to occupy 30 wt% of the solvent. In Example 15, the same polymer component as in Example 1 was added to the electrolyte to occupy 40 wt% of the solvent. In Example 16, the same polymer component as in Example 1 was added to the electrolyte to occupy 50 wt% of the solvent.
[0140] (Withstand voltage test) The withstand voltage of the solid electrolytic capacitors in Examples 13 to 16 was measured. The measurement method and conditions for withstand voltage were the same as in Example 1. The measurement results for withstand voltage, including Example 1, along with the amount of polymer component added, are shown in Table 4 below.
[0141] (Table 4) TIFF2026165968000007.tif61161
[0142] As shown in Table 4 above, increasing the polymer content in the electrolyte solvent improves the voltage withstand capability of the solid electrolytic capacitor. In particular, it was confirmed that the voltage withstand capability of the solid electrolytic capacitor increases further when the polymer content in the solvent exceeds 20 wt%.
[0143] (Examples 17 to 20) Solid electrolytic capacitors were fabricated in Examples 17 to 20. In Example 15, an alkylene oxide-added glycerol derivative with a molecular weight of 3000 was added as a polymer component to the solvent at a concentration of 40 wt%. In contrast, the solid electrolytic capacitors of Examples 17 to 20 differ in the type of polymer component added to the electrolyte solvent. Except for the difference in the type of polymer component, the solid electrolytic capacitors of Examples 17 to 20 had the same configuration as Example 15 and were fabricated using the same manufacturing method and conditions.
[0144] In Example 17, polyethylene glycol with a molecular weight of 200 was added to the electrolyte as a polymer component, accounting for 40 wt% of the solvent. In Example 18, polyethylene glycol with a molecular weight of 300 was added to the electrolyte as a polymer component, accounting for 40 wt% of the solvent. In Example 19, polyethylene glycol with a molecular weight of 600 was added to the electrolyte as a polymer component, accounting for 40 wt% of the solvent. In Example 20, polyethylene glycol with a molecular weight of 1000 was added to the electrolyte as a polymer component, accounting for 40 wt% of the solvent.
[0145] (Withstand voltage test) The withstand voltage of the solid electrolytic capacitors in Examples 17 to 20 was measured. The measurement method and conditions for withstand voltage were the same as in Example 1. The measurement results for withstand voltage, including Example 15, along with the type of polymer component, are shown in Table 5 below.
[0146] (Table 5) TIFF2026165968000008.tif83167
[0147] As shown in Table 5 above, the solid electrolytic capacitor of Example 15 had the highest voltage withstand capability among the test samples. In other words, it was confirmed that a polyol or derivative thereof with a molecular weight of 600 or more and to which alexylene oxide has been added is preferred as the polymer component.
[0148] (Examples 21 to 26) Solid electrolytic capacitors were fabricated in Examples 21 to 26. In Example 2, a conductive polymer liquid containing ethylene glycol was used in the solid electrolyte formation process, leaving residual ethylene glycol in the solid electrolyte. The solid electrolytic capacitors of Examples 21 to 26 differ in the amount of ethylene glycol added to the conductive polymer liquid. Therefore, the solid electrolytic capacitors of Examples 21 to 26 differ in the ethylene glycol content in the solid electrolyte layer. Except for the difference in the amount of compound containing a hydroxyl group and a boiling point of 150°C or higher added, the solid electrolytic capacitors of Examples 21 to 26 had the same configuration as Example 2 and were fabricated using the same manufacturing method and under the same manufacturing conditions.
[0149] In Example 21, ethylene glycol was not added to the conductive polymer solution. In Example 22, ethylene glycol was added to the conductive polymer solution to account for 10 wt%. In Example 23, ethylene glycol was added to the conductive polymer solution to account for 15 wt%. In Example 24, ethylene glycol was added to the conductive polymer solution to account for 30 wt%. In Example 25, ethylene glycol was added to the conductive polymer solution to account for 50 wt%. In Example 26, ethylene glycol was added to the conductive polymer solution to account for 70 wt%.
[0150] (Withstand voltage test) The withstand voltage of the solid electrolytic capacitors in Examples 21 to 26 was measured. The measurement method and conditions for withstand voltage were the same as in Examples 1 to 4. The measurement results for withstand voltage, along with the amount of ethylene glycol added, are shown in Table 6 below. In the table, EG represents ethylene glycol.
[0151] (Table 6) TIFF2026165968000009.tif71161
[0152] As shown in Table 6 above, the withstand voltage of the solid electrolytic capacitors in Examples 22 to 26 is higher than that of Example 21. In Examples 22 to 26, ethylene glycol was added to the conductive polymer liquid, and the solid electrolyte layer contained ethylene glycol. This confirmed that the withstand voltage of the solid electrolytic capacitor is further improved when a compound having a hydroxyl group and a boiling point of 150°C or higher, such as ethylene glycol, is included in the solid electrolyte layer of the solid electrolytic capacitor. [Explanation of Symbols]
[0153] 1 Smoothing circuit 2 diodes 3. Solid electrolytic capacitors 4. Inrush current limiting circuit 41 Resistors 42 switches 5. Filter Circuit 10S plane 10e1 edge 10e2 edge 10A end area 10B Foil surface area 11 Anode Leads
Claims
1. Anode foil having a dielectric film with a voltage withstand capability of 300V or more, A cathode body facing the anode foil, A conductive polymer containing sulfur in its molecular structure is interposed between the anode foil and the cathode body, Equipped with, The sulfur intensity ratio per unit area adhering to the edge region of the anode foil is 1.92 or less compared to the sulfur per unit area adhering to the foil surface region other than the edge region. A solid electrolytic capacitor characterized by the following features.
2. The sulfur intensity ratio is 1.71 or less. A solid electrolytic capacitor according to claim 1, characterized by the above.
3. Furthermore, equipped with an electrolyte, The electrolyte contains 20 wt% or more of a polymer component in the total amount of the electrolyte. A solid electrolytic capacitor according to claim 1 or 2, characterized by the above.
4. The polymer component is a polyol or a derivative thereof having one or more alkylene oxide groups added and a molecular weight of 600 or more. A solid electrolytic capacitor according to claim 3, characterized by the above.
5. A solid electrolyte layer containing the conductive polymer is formed, The solid electrolyte layer contains a compound having a hydroxyl group and a boiling point of 150°C or higher. A solid electrolytic capacitor according to claim 1 or 2, characterized by the above.
6. The compound is ethylene glycol, diethylene glycol, triethylene glycol, polyoxyethylene glycol, glycerin, polyglycerin, or a combination of these. A solid electrolytic capacitor according to claim 5, characterized by the above.
7. The solid electrolytic capacitor described in claim 1 is provided, A smoothing circuit characterized by the following.
8. The solid electrolytic capacitor described in claim 1 is provided, A filter circuit characterized by the following.
9. A process for forming an anode foil, A cathode body formation process for forming a cathode body, The process of forming an electrolyte layer on the surface of the anode foil, wherein a conductive polymer containing sulfur in its molecular structure is arranged. Includes, The anode foil formation step includes a chemical conversion step in which a dielectric film with a dielectric strength of 300V or more is formed on the anode foil by a chemical conversion treatment with an applied voltage of 300V or more. The electrolyte layer formation step includes an adjustment step of adjusting the sulfur intensity ratio per unit area attached to the edge region of the anode foil to be 1.92 or less compared to the sulfur intensity per unit area attached to the foil surface region other than the edge region. A method for manufacturing solid electrolytic capacitors characterized by the following.
Citation Information
Patent Citations
Conductive polymer and solid electrolytic capacitor using the same
JP2003160647A
Solid electrolyte, and solid electrolytic capacitor using the same
JP2008258224A